Influence of Sitting Positions and Level of Trunk Control During Reaching Movements in Late Preterm and Full-Term Infants - Sato, Natália T. da Silva; Tudella, Eloisa (Frontiers in Pediatrics, 2018)
In order to acquire reaching and independent sitting, refinement of trunk control is needed by gradually and progressively incorporating the head, thoracic, lumbar and sacral segments. Previous studies have evaluated trunk control in a segmental way, standardizing the level of manual support in the infants´ trunk during reaching. The aim of this study was to identify the level of trunk control and to analyze the influence of the difference sitting positions in late preterm and full-term infants between 6 and 8 months of age during reaching. Therefore, 36 infants born full term (control group) - FTG and 20 late preterm infants at a corrected age (experimental group) - PTG were evaluated. Most of the infants started the study at 6 months and they were evaluated monthly until 8 months of age (longitudinal study) in a total of 1 to 3 visits. The Segmental Assessment of Trunk Control was used to identify the level of trunk control in a segmental way, as well as to verify the capacity of the infant to maintain or regain the vertical position while sitting. Kinematic analysis was used for reaching. The infants were in a ring sitting position and at 90° of flexion. To elicit reaching, an attractive object was presented at the infant´s midline and at 45º to the right and left. We found that PTG infants presented lower trunk control scores, i.e., worse control. For both groups, the ring sitting position and at 90° of flexion did not influence most kinematic variables during reaching because accurate manual support was provided for the infants´ trunk. The PTG group presented less trunk displacement when at 90° of flexion. Compared to the FTG, even with accurate trunk support, the PTG group presented more immature reaches. These results suggest that accurate manual trunk support favored more stability of the trunk during the reach. Thus, early intervention is suggested for PTG infants and reaching in this age group should be trained in the ring sitting position with their trunk accurately manually supported. SATCo is an effective tool for segmental trunk evaluation.